Improvement of Presbyopia, Dry Eye, Intraocular Pressure, and Near Vision Through Cassiae Tea Consumption - Mei Fan; Jen-Lin Hung; Shao-Huan Hung; Li-Chai Chen; Chi-Ting Horng (Medicina)
Background and Objectives: This study aimed to illustrate a novel method for improving presbyopia by drinking cassiae tea. Materials and Methods: A total of 425 eyes from 425 participants (aged 52.5 ± 9.5 years) were recruited and divided into several experimental groups over a 6-month period. Participants consumed cassiae tea daily (10 g of cassiae semen brewed in 500 cc of water). Meanwhile, control group participants consumed 500 cc of plain water along with 1000 mg of vitamin C each day. Experiments 1 and 2: Participants with severe dry eye and intraocular pressure (IOP) > 30 mmHg were enrolled, and outcomes were assessed for these conditions, respectively. Experiments 3, 4, and 7: These experiments evaluated pupil size, near vision, and serum superoxide dismutase (SOD) levels in two groups of volunteers. Experiment 5: Different quantities of cassiae tea were prescribed to various groups, and near vision was measured. Experiment 6: Three questionnaires assessed presbyopic symptoms after cassiae tea consumption. Experiment 8: The antioxidant activity of cassiae tea compared with other bioactive compounds and Chinese herbs was evaluated using the DPPH test. Results: By the fourth month of the study, participants experienced increased tear volume and reduced IOP. Pupil size constricted, near vision improved, and serum SOD levels increased. Furthermore, greater consumption of cassiae tea was correlated with better near vision. The antioxidant activity of cassiae tea was found to surpass that of anthocyanins, wolfberry, and vitamin C. Conclusions: Drinking cassiae tea improves dry eye symptoms, reduces IOP, regulates pupil size, and enhances near vision due to its excellent antioxidant and pharmacological properties. These benefits may particularly aid individuals with presbyopia and those engaged in near-distance activities, such as smartphone use.